2013
DOI: 10.1371/journal.pgen.1003672
|View full text |Cite
|
Sign up to set email alerts
|

The Mating Competence of Geographically Diverse Leishmania major Strains in Their Natural and Unnatural Sand Fly Vectors

Abstract: Invertebrate stages of Leishmania are capable of genetic exchange during their extracellular growth and development in the sand fly vector. Here we explore two variables: the ability of diverse L. major strains from across its natural range to undergo mating in pairwise tests; and the timing of the appearance of hybrids and their developmental stage associations within both natural (Phlebotomus duboscqi) and unnatural (Lutzomyia longipalpis) sand fly vectors. Following co-infection of flies with parental lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
143
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(153 citation statements)
references
References 37 publications
5
143
0
5
Order By: Relevance
“…Furthermore, the 3n and 4n DNA contents were maintained in the hybrids throughout numerous in vitro passages as promastigotes and after recovery of tissue amastigotes from infected mice, suggesting that the polyploidy is not intrinsically unstable. As with all of the Leishmania intraspecies hybrids described previously (18,20), analysis of markers on the maxicircle DNA indicates that kDNA inheritance was uniparental and that either parent could contribute kDNA to the progeny. Although a similar conclusion was accorded the inheritance of maxicircle polymorphisms in hybrid progeny of Trypanosoma brucei, subsequent analyses at an earlier stage of hybrid generation indicated that kDNA inheritance was biparental, with segregation of maxicircles during subsequent mitotic divisions (28).…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Furthermore, the 3n and 4n DNA contents were maintained in the hybrids throughout numerous in vitro passages as promastigotes and after recovery of tissue amastigotes from infected mice, suggesting that the polyploidy is not intrinsically unstable. As with all of the Leishmania intraspecies hybrids described previously (18,20), analysis of markers on the maxicircle DNA indicates that kDNA inheritance was uniparental and that either parent could contribute kDNA to the progeny. Although a similar conclusion was accorded the inheritance of maxicircle polymorphisms in hybrid progeny of Trypanosoma brucei, subsequent analyses at an earlier stage of hybrid generation indicated that kDNA inheritance was biparental, with segregation of maxicircles during subsequent mitotic divisions (28).…”
Section: Discussionmentioning
confidence: 60%
“…DNA content analysis of the hybrid clones revealed that the 11 independent crosses produced five 2n, five 3n, and a single 4n progeny. Triploid progeny have also been observed for many of the L. major intraspecies hybrids described (18,20). Based on the relative intensities of SNP-CAPS digestion products, we concluded that at least part of the extra set of chromosomes could be contributed by either parent.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The results are especially convincing for Leishmania (Boité et al, 2012;Downing et al, 2011;Inbar et al, 2013;Lachaud et al, 2014;Mannaert et al, 2012;Rogers et al, 2011Rogers et al, , 2014Sterkers et al, 2011Sterkers et al, , 2012Sterkers et al, , 2014, but are also available for T. cruzi (Buscaglia et al, 2015;Minning et al, 2011;Reis-Cunha et al, 2015;Souza et al, 2011). Aneuploidy is also frequent in C. albicans and C. neoformans (Ene and Bennet, 2014;McManus and Coleman, 2014;Ni et al, 2013).…”
Section: A Debate In the Debate: Unisex/selfing/ Inbreeding Versus 'Smentioning
confidence: 96%